2022
DOI: 10.3389/fgene.2022.864092
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks for Classification and Image Generation of Aging in Genetic Syndromes

Abstract: Background: In medical genetics, one application of neural networks is the diagnosis of genetic diseases based on images of patient faces. While these applications have been validated in the literature with primarily pediatric subjects, it is not known whether these applications can accurately diagnose patients across a lifespan. We aimed to extend previous works to determine whether age plays a factor in facial diagnosis as well as to explore other factors that may contribute to the overall diagnostic accurac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…Machine learning approaches to facial analysis have been seen as a means to improve diagnostic capabilities in understudied populations (Kruszka, Tekendo‐Ngongang, & Muenke, 2019). For example, Williams syndrome and 22q11.2 deletion syndrome are typically diagnosed in the pediatric age group, and a facial analysis neural network classifier built to help diagnose these conditions in older individuals outperformed clinical geneticists across five different age groups, with overall accuracy gains over clinical geneticists of 15.5 and 22.7%, respectively (Duong et al, 2022). Another facial analysis application for the autosomal dominant disorder Rubinstein‐Taybi syndrome (RSTS), however, showed poor discrimination efficacy in an African group while demonstrating excellent discrimination efficacy in a European one (Tekendo‐Ngongang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning approaches to facial analysis have been seen as a means to improve diagnostic capabilities in understudied populations (Kruszka, Tekendo‐Ngongang, & Muenke, 2019). For example, Williams syndrome and 22q11.2 deletion syndrome are typically diagnosed in the pediatric age group, and a facial analysis neural network classifier built to help diagnose these conditions in older individuals outperformed clinical geneticists across five different age groups, with overall accuracy gains over clinical geneticists of 15.5 and 22.7%, respectively (Duong et al, 2022). Another facial analysis application for the autosomal dominant disorder Rubinstein‐Taybi syndrome (RSTS), however, showed poor discrimination efficacy in an African group while demonstrating excellent discrimination efficacy in a European one (Tekendo‐Ngongang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common applications of artificial intelligence (AI) in clinical genetics is the use of facial analysis technology. A recent study showed that a neural network classifier outperformed the average clinical geneticists in recognizing two common genetic conditions (Duong et al, 2022). Like any AI platform, accuracy greatly depends on the data set used to train the algorithm.…”
Section: Algorithm Comparison Group Aucmentioning
confidence: 99%
“…The concept of a precise diagnosis is fueling an interest in testing newborns for conditions beyond the current limited newborn screening programs (Gold et al, 2023). Recently, Duong et al using a neural network classifier showed that their algorithm was able to accurately distinguish between Williams syndrome and 22q11.2 deletion syndrome across all ages, including infants (Duong et al, 2022). Research in the accuracy of facial analysis technology in newborns, especially in conditions with actionable findings, would be of value in resource limited settings where other screening modalities are not always available.…”
Section: Algorithm Comparison Group Aucmentioning
confidence: 99%
“…The last decade has witnessed an unprecedented increase in interest in applications of AI to medicine and biomedical sciences, and a surge in AI translational research initiatives in medical genetics and genomics (Duong et al, 2022; Poplin et al, 2018). Specifically, machine learning methods are being applied successfully for diagnostic processes involving pattern recognition, and the increasing use of computer‐assisted facial images processing for genetic syndromes recognition is a perfect illustration of how machine learning methods are being applied to dysmorphology (Hsieh et al, 2022; Kruszka et al, 2019).…”
Section: The Future Of Dysmorphology: a Global Perspectivementioning
confidence: 99%